A Library Network is born across the sea - Dedetzi, Panagiota; Brindesi, Hara; Kraniotou, Katia; Kalligeros, S.; Kouri, Stavroula; Katsirikou, Anthi; Thanopoulou, Helen A.; Despotopoulou, Nektaria (Qualitative and Quantitative Methods in Libraries, 2019)
The presentation focuses on the establishment of a new thematic library network in Greece encompassing the majority of organized maritime orientated collections within special and/or University libraries: The Maritime Libraries Network (MarLiNet). The Network originated from the initial cooperation of three libraries with significant maritime collections, namely those of the Eugenides Foundation Library, the Aikaterini Laskaridis Foundation Library and the Library of the University of the Aegean about a decade ago. The interest of the three institutions to cooperate on the maritime transport collections resulted in the signing, in 2010, of a first Memorandum of cooperation and in the establishment of the “Triangle of Maritime Libraries” with the written intent for it to become one day a “Polygon”. Today, the network consists of 8 libraries 1. Aikaterini Laskaridis Foundation 2. Eugenides Foundation 3. Hellenic Maritime Museum 4. Hellenic Naval Academy 5. National Technical University of Athens 6. University of Piraeus 7. University of the Aegean 8. Naval History Department (Hellenic Navy) These libraries, possessing important maritime collections and sharing the common vision of improving their services to their research and general readers (users), meet regurarly on a monthly basis through their representatives in order to coordinate the actions of the network. The paper provides an overview of the vision, the values and the main purposes underlying the cooperation of the MarLiNet. These are mainly: a. Expanding the availability of titles to their users b. Saving resources through a rationalized strategy of new acquisitions c. Increasing the readability of their shipping collections; and d. maximizing their visibility as important collections on maritime transport subjects, a step already taken through the on-going construction of a joint website. In the above context, we are discussing in this presentation our short-term and long-term planning as well as our strengths, weaknesses and the challenges that this network offers. Finally, there is reference to some best practices and lessons learned by other relevant initiatives.